New-onset autoimmune disease after COVID-19 - Hileman, Corrilynn O.; Malakooti, Shahdi K.; Patil, Nirav; Singer, Nora G.; McComsey, Grace A. (Frontiers in Immunology, 2024)
Introduction SARS-CoV-2 may trigger autoimmune disease (AD) through initial innate immune activation with subsequent aberrations in adaptive immune cells leading to AD. While there are scattered reports of incident AD diagnosed after COVID-19, the risk in context of key circulating strains is unknown. Methods TriNetX, a global, federated, health research network providing access to electronic medical records across 74 healthcare organizations, was utilized to define an adult cohort between January 1, 2020-March 3, 2023. Exposure was defined as COVID-19 diagnosis (ICD-10 code or positive laboratory test). Age-, sex-propensity score-matched controls never had COVID-19 diagnosed. Outcomes were assessed one month to one year after index date. Patients with AD prior to or within one month after index date were excluded from primary analysis. Incidence and risk ratios for each AD were assessed. Results 3,908,592 patients were included. Of 24 AD assessed, adjusted risk ratios for eight AD were higher for patients who had COVID-19 compared to those who did not. Cutaneous vasculitis (aHR:1.82; 95%CI:1.55-2.13), polyarteritis nodosa (aHR:1.76; 95%CI:1.15-2.70) and hypersensitivity angiitis (aHR:1.64; 95%CI:1.12-2.38) had the highest risk ratios. Overall, psoriasis (0.15%), rheumatoid arthritis (0.14%), and type 1-diabetes (0.13%) had the highest incidence during the study period and of these, psoriasis and diabetes were more likely after COVID-19. Discussion Risk of any AD was lower if COVID-19 was diagnosed when Omicron variants were the predominate circulating strains. A positive antinuclear antibody was more likely and predictive of AD after COVID-19.SARS-CoV-2 may be a potential trigger for some AD, but risk for AD may decrease with time given apparent lower risk after infection with Omicron variants.